Pengaruh Pengetahuan Dasar Matematika Terhadap Keyakinan Epistemologis dan Minat Belajar Matematika Siswa : The Influence of Basic Mathematical Knowledge on Students’ Epistemological Beliefs and Interest in Learning Mathematics - Khatimah, Ummi Khusnul; Sangila, Muhammad Syarwa; Agus, Imaludin; Riansyah, Firman (Lembaga Bale Literasi, 2025)
This study aims to investigate the relationship between Basic Mathematical Knowledge (BMK) and students' epistemological beliefs and interest in learning mathematics among seventh-grade students at MTs Negeri 3 Konawe. Descriptive analysis and multivariate regression were employed as the research methods. The findings indicate that students’ BMK is relatively high, with an average score of 27.48 out of a maximum of 32. Furthermore, students demonstrated positive epistemological beliefs and a good level of interest in learning mathematics. However, regression analysis revealed that BMK does not have a significant effect on epistemological beliefs (regression coefficient = -0.053; p = 0.821) or on interest in learning mathematics (regression coefficient = -0.309; p = 0.342). These results suggest that affective factors, learning experiences, and learning environments play a more substantial role in shaping students' beliefs and interests than basic cognitive knowledge. Therefore, the study recommends implementing more contextual and affective-based learning approaches to foster students’ motivation and beliefs in learning mathematics.